Pinpointing when T cell costimulatory receptor CTLA-4 must be engaged to dampen diabetogenic T cells - Lühder, Fred (The National Academy of Sciences, 2000)
Engagement of the T cell costimulatory receptor CTLA-4 can potently down-regulate an immune response. For example, in a T cell receptor transgenic mouse model of autoimmune diabetes, CTLA-4 interactions keep pancreatic islet-reactive T cells in check, evidenced by the finding that mAb blockade of CTLA-4 rapidly provokes diabetes in animals that would not normally succumb until many months later. Interestingly, this effect is only observed early in the course of disease, before insulitis is stably entrenched. Here, we have exploited a highly synchronous and easily manipulable transfer system to determine precisely when CTLA-4 must be engaged to check the diabetogenicity of islet-reactive T cells. Our results indicate that CTLA-4 interactions during initial priming of the T cells in the pancreatic lymph nodes are not determinant. Rather, the critical interactions occur when the T cells secondarily reencounter their antigen in the target organ, the pancreatic islets. In addition, we made use of CTLA-4-deficient mice to bolster our interpretation that CTLA-4 engagement has a dampening rather than an enhancing influence on diabetes progression.